Scientific Examination of Halal and Haram Animals in the Quran: Implications for Modern Dietary Practices - Dr Adeeba Siddiqui; Shafqat Naz; Maryam Fatima (Journal of Religion and Society, 2025)
It discusses the scientific analysis of halal and haram animals, reviewed by the Quran, along with their characteristics and effects on health and nutrition. Based on Islamic religion, the Quranic dietary laws state what animals Muslims can and cannot eat to maintain cleanliness and good health. According to science, all halal-designated animals carry traits and nutrition that ensure their consumption is safe and beneficial for health. On the other hand, since animals like swine and carnivores can contain parasites, toxins and diseases, their consumption is forbidden. It also emphasizes that halal methods of slaughter ensure both the safety of foods and well-being of animals as per scientific guidelines. By using scientific knowledge, Islamic jurists can improve the significance of halal rules in today’s food business and deal with challenges such as certification, mixing unapproved food products and educating people about halal dietary laws. Connecting religious teachings with facts from science demonstrates that a halal diet is practical, ethical and based on both religion and science. Lastly, the article urges people in charge to join efforts to keep halal products safe and secure for world consumers and the public’s health. As a result of this work, people now have a better grasp of how halal and haram food laws work and, as a result, have more opportunities to eat better and healthier in line with Muslim traditions.. Keywords: Islamic Teaching, Labor Rights, Dignity, Social Justice, Polices